An epidemiological study of tick-borne diseases and their effects on productivity of Zebu cattle under traditional management on Rusinga Island, western Kenya - Latif, A.A.; Rowlands, G.J.; Punyua, D.K.; Hassan, S.M.; Capstick, P.B. (Elsevier, 1995)
Ten farmers on Rusinga Island, Lake Victoria, Kenya were selected to study the epidemiology of tick-borne diseases (TBDs) and their possible effects on calf performance. During the years 1986-1988 a total of 162 calves were ear-tagged, weighed monthly and monitored closely for TBDs and endoparasitism. The mean (plus minus SD) body weights at 4 months, 8 months and 12 months were 35 plus minus 7 kg, 47 plus minus 10 kg and 61 plus minus 12 kg, respectively. The average growth rate from birth to 12 months of age was 120 g day minus 1, but there were significant effects of year, season of birth and farm on calf liveweight gain. Calf mortality from birth to 12 months of age was high, ranging from 17 to 56 percent among farms, and averaging 33 percent. Twenty one percent of mortalities were diagnosed as due to East Coast fever (ECF) and 14 percent as due to endoparasites. The average annual ECF incidence rate was 22 percent and the ECF case fatality rate 21 percent, but these deaths were recordes on only two of the ten monitored farms. Forty-nine percent of dams had one or more damaged teats due to the tick species Amblyomma variegatum. Attempts were made using this small data set to analyse for effects of ECF and number of damaged teats on calf performance but no statistically significant effects could be demonstrated.